Analysis of The Influence of E-Service Quality and Brand Awareness on Customer Satisfaction of Marketplace Bukalapak - Betty Rahayu; D. Yadi Heryadi; Yulia Novita; Dahlia Nopelina Siallagan; Syamsulbahri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study aims to investigate how brand perception and the quality of an e-service impact customer satisfaction. This kind of research is quantitative. An online shopping sample was employed to gather the fundamental data for this investigation. The survey was distributed to 100 marketplace users in order to acquire data through unintentional sampling. The investigation's methodology is multiple regression analysis. According to the study's findings, customer satisfaction is significantly influenced by brand image, e-service quality, and brand image.